Classification and Characteristics of Issues that are Considered and Resolved During the Execution of Court Decisions in Criminal Proceedings - Vapnyarchuk, Anastasia (Problems of legality, 2026)
The study of issues that are considered and resolved during the execution of court decisions in criminal proceedings, and in particular the features of their classification and the characteristics of their varieties according to various criteria, is important both for the science of criminal procedure and for the practice of law enforcement. After all, a correct understanding of the legal nature of the varieties of such issues allows for the proper and effective implementation of criminal procedural activities at the stage of execution of court decisions, and therefore contributes to a faster achievement of the goal of criminal proceedings in general and the fulfillment of its tasks in particular. The purpose of the article is a critical analysis of approaches to the classification of issues that are resolved during the execution of court decisions, which take place in the domestic scientific literature, and the expression of the author’s position on dividing them into varieties according to various criteria and the characteristics of individual ones. In the work, thanks to the use of a system of scientific knowledge methods, this goal was achieved. The results of the study consist in expressing support for the scientific position on the need to distinguish two stages of the stage of execution of court decisions: first, the appeal of the court decision for execution; second, consideration and resolution of issues related to the execution of court decisions. Based on the analysis of the regulatory regulation of both stages of the stage of execution of court decisions and law enforcement practice, it is concluded that the second stage is the main content of this stage. In addition, the work has classified the issues that are considered and resolved at the stage of execution of court decisions according to various criteria, and characterized the legal nature of some of them. In the study, for the first time in the domestic criminal procedural doctrine, the possibility of dividing issues according to a number of different criteria has been proposed, in particular: depending on the nature of the circumstances that determine their resolution; on the behavior of the convicted person, which determines the resolution of certain issues; on the legal nature of the issues that arise; on the presence of a direct connection with achieving the goal of punishment. The greatest research attention was paid to the classification and characterization of issues considered and resolved in the execution of court decisions, depending on the nature of the impact of judicial control activities on the court’s decisions (on corrective and concretizing and the allocation of corrective and concretizing judicial control) and depending on the form of the impact of judicial control activities on the rights of persons to whom they relate (law-enforcing and law-restricting and the definition of law-enforcing and law-restricting judicial control).